1995
DOI: 10.1074/jbc.270.2.515
|View full text |Cite
|
Sign up to set email alerts
|

Protective Protein as an Endogenous Endothelin Degradation Enzyme in Human Tissues

Abstract: An enzyme hydrolyzing the carboxyl terminus of endothelin-1 was detected in control human tissues but was deficient in tissues from a patient with galactosialidosis, a metabolic disease caused by the protective protein gene mutation. It was proportional to the amount of immunologically estimated mature protective protein. An antibody against the lysosomal protective protein/beta-galactosidase complex precipitated the enzyme activity almost completely. Transfection of the human cDNA for protective protein resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 35 publications
0
29
1
1
Order By: Relevance
“…In particular, the components of the multienzyme complex, Neu1, CathA, and ␤-galactosidase (or its alternatively spliced elastin-binding form), participate in processing of endothelin-1 (21,33), assembly of the elastic fibers (21,34,35), pro-inflammatory response in macrophages (36), migration, invasion, and adhesion of cancer cells (37), proliferation of aortic smooth muscle cells (38), and exocytosis (39). In humans, genetic defects in CathA cause disruption of the complex and trigger galactosialidosis (MIM 256540), a severe multisystemic disease characterized by combined deficiency of Neu1, ␤-galactosidase, and CathA (for review, see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the components of the multienzyme complex, Neu1, CathA, and ␤-galactosidase (or its alternatively spliced elastin-binding form), participate in processing of endothelin-1 (21,33), assembly of the elastic fibers (21,34,35), pro-inflammatory response in macrophages (36), migration, invasion, and adhesion of cancer cells (37), proliferation of aortic smooth muscle cells (38), and exocytosis (39). In humans, genetic defects in CathA cause disruption of the complex and trigger galactosialidosis (MIM 256540), a severe multisystemic disease characterized by combined deficiency of Neu1, ␤-galactosidase, and CathA (for review, see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in the lysosome, CAPP has also been shown to inactivate endothelin, a potent SMC vasoconstrictor and mitogen (41,42). Interestingly, a previous report demonstrated that atRA antagonized endothelin-induced SMC mitogenesis through the attenuation of ERK activity (9).…”
Section: Fig 5 Tissue-restricted Expression Of Risc Mrna Total Rnamentioning
confidence: 99%
“…7,13 Studies of cultured fibroblasts from galactosialidosis patients demonstrated that these cells lack endothelin-degrading capacity, whereas brain autopsies showed high ET-1-specific immunoreactivity. 14,15 Because in tissues and in the circulation, ET-1 is also cleaved by an abundant neutral endopeptidase, NEP, 16 in vivo experiments are required to understand whether CathA is a nonredundant ET-1-degrading enzyme. The previously described CathA-knockout mice are not suitable for physiological and behavioral studies because they develop progressive and diffuse edema, tremor, and ataxia due to secondary Neu1 deficiency.…”
mentioning
confidence: 99%